EFFECTIVENESS OF CRIMINAL CRIMINAL INVESTIGATIONS IN HOUSEHOLD IN PALOPO POLICE LAW AREA - Andi Ahmad Akbar; Hambali Thalib; Sufirman Rahman (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal